Developing an integrated and comprehensive training strategy for public sector leaders: The French experience. Issue 1 (March 2017) - Larat, Fabrice
Because of their tasks and their high level of responsibilities, leadership aptitudes, besides managerial competences, are key for civil servants who will occupy top positions. The institutions in charge of their training and education must not only provide the leaders of tomorrow with the knowledge and skills they need to do their current job properly; they must also ensure that the leaders have the qualities required for the exercise of their responsibilities at all stages of their professional career. Based on the experience of the French national school of public administration (ENA) and its key role as the training organisation both for pre-service and lifelong learning for French public sector executives, this paper presents the different elements of the French approach for training future government administrative leaders. This comprehensive and integrated strategy takes into consideration the challenges of training for leadership and the needs for a permanent adaptation to the evolution of the administrative environment.